“Fungsi Minyak Sebagai Penyembuh (Studi Eksegetis Injil Markus 6:13 dan Surat Yakobus 5: 14)”. - Defi Ratna Sari Sihaloho (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
Target of this research is to know oil function as healer pursuant to epistle of Markus 6:13 and Letter of Yakobus 5: 14. Research method in writing of this erudite masterpiece is method qualitative namely with approach of study of eksegetis. In this peneltian will dig by oil function as healer in epistle of Markus 6:13 and Letter of Yakobus 5: 14 and cite other sentences related to nats dug, and also compare opinion all expert and analysing him/ it, later;then see its bearing. done/conducted Interpretation method it is of course by using stages;steps and condition interpretation of Bible, so that stages;steps weared by researcher shall be as follows: recognition of buku, text analysis, literal translation, common/ public context and special context, sentence interpretation per sentence, and skopus. Result of from study of eksegetis epistle of Markus 6:13 and Letter of Yakobus 5: 14 is oil have function as healer media to ill, which accompanied by the name of God. Keyword : Function, Oil, Healer